Chapter Epigraphic Stratigraphy: is There Any Trace of the Ostrogoths in Early Medieval "Layers" (6th-9th Century)? - Frauzel, Flavia (Reti Medievali E-Book, 2022)
The short but significant experiment of the Ostrogothic Kingdom in Italy left politically ephemeral albeit culturally surprisingly durable traces in the peninsula. Among them, epigraphy takes centre stage when discussing decrees, laws, and public documents, which are a direct expression of the rulers' will to gain greater visibility and disseminate their voice. However, epigraphy is also crucial to knowing the names, professions, ideas, and other concepts relating to the ordinary people. This contribution aims to examine a number of issues concerning controversial Germanic names datable between the VIth and VIIth century AD, and variably assigned to Ostrogoths, Lombards, and even Carolingians characters; through the lens of these durable materials, which - ironically enough - are monuments both recording contemporary propaganda and everyday life facets, the article will also explore the graphic and epigraphic changes which occurred in Italy between the VIth-IXth centuries.